The role of firms' location on persistency of various types of innovation - Charlie Karlsson; Sam Tavassoli (European Regional Science Association (ERSA), 2016)
This paper analyzes the role of regional characteristics on innovation persistency among firms. Using five waves of the Community Innovation Survey in Sweden, we have traced the innovative behavior of firms over a ten-year period, i.e. between 2002 and 2012. On the one hand, we distinguish between four types of innovations: process, product, marketing, and organizational innovations. On the other hand, we considered various regional characteristics including knowledge stock, market thickness, and extent of knowledge spillovers. Using a dynamic Probit model, we found that, in general, those firms located in the regions with higher stock of knowledge, thicker market, and higher extent of knowledge spillovers exhibit higher probability of being a persistent innovators. Such higher persistency is mostly pronounced for product innovators.
Keywords: D22; L20; O31; O32; 330; location; persistence; innovation; product innovations; process innovations; market innovations; organizational innovations; firms; Community Inno¬vation Survey